Rupture characteristics of major and great (Mw ≥ 7.0) megathrust earthquakes from 1990 to 2015: 2. Depth dependence. Issue 2 (18th February 2016) - Ye, Lingling; Lay, Thorne; Kanamori, Hiroo; Rivera, Luis
Abstract: Depth‐varying characteristics of high‐frequency seismic radiation for megathrust earthquakes have been inferred from several recent giant earthquakes and large tsunami earthquakes. To quantify any depth dependence more extensively, we analyzed 114 Mw  ≥ 7.0 thrust‐faulting earthquakes with centroid depths from 5 to 55 km on circum‐Pacific megathrusts using teleseismic body wave finite‐fault inversions and source spectrum determinations. Large tsunami earthquakes and some other shallow events at depths less than about 18 km have unusually long source durations, and low values of static stress drop (Δ σE ), Vr 3 Δ σE, and apparent stress, with relatively depleted high‐frequency radiation. Deeper events have no clear global trend with source depth for moment‐normalized centroid time or total duration, static stress drop, moment‐scaled radiated energy, apparent stress, or radiation efficiency. Regional behavior among the 17 sampled subduction zones generally conforms to the global composite. The source spectra have high‐frequency logarithmic spectral decay slopes averaging ~ −1.6. There is relative enrichment in high‐frequency spectral levels with increasing source depth manifested in reduced high‐frequency spectral decay slope. The ratio of high‐frequency (0.3–1 Hz) radiated energy to total energy increases correspondingly. These observations suggest that overall dynamic rupture processes are relatively insensitive to source depth, but varying scale lengths of megathrust heterogeneity may contribute to modest enrichment of high‐frequency seismic radiation for events deeper on the megathrust. A weak correlation of higher estimated average megathrust temperature at 30 km depth with higher spectral decay rate indicates that the depth‐varying pattern may in part result from frictional properties being influenced by temperature variations or by systematic reduction of average attenuation with increasing depth along the megathrust. Key Points: Source parameters for 114 major megathrust ruptures are examined for depth dependence Shallow events, including tsunami earthquakes, have low stress drop and apparent stress The relative amount of high‐frequency energy increases with source depth but not total energy